Cationic collector conformations on an oxide mineral interface: Roles of pH, ionic strength, and ion valence. (1st May 2020) - Solongo, Stephen Kayombo; Gomez-Flores, Allan; You, Junhyuk; Choi, Sowon; Heyes, Graeme W.; Ilyas, Sadia; Lee, Jangchoon; Kim, Hyunjung
Graphical abstract: Highlights: Conformational changes of BTAC on a silica surface was studied using QCM-D. The presence of NaCl led to a thin, rigid layer (low dissipation). A thick, soft layer (high dissipation) formed in the presence of CaCl2 . Structural conformational change of BTAC was sensitive to pH and ionic strength. Strong correlation was observed between hydrophobicity and ΔD/Δf ratio. Abstract: The adsorption of collectors at the solid–liquid interface to impart and enhance a mineral's hydrophobicity is essential to mineral froth flotation. During adsorption, collectors must conform on the mineral surface with their nonpolar tails facing the aqueous phase to enhance the mineral's hydrophobicity. This conformation is subject to conditions prevailing in the aqueous phase, such as the pH and nature of ions present. Since this conformation can affect the degree of hydrophobicity, molecular-level understanding of this phenomenon also is beneficial to improve hydrophobicity via adsorption layer manipulation. In this study, the structural conformational changes of cationic collector behenyl trimethyl ammonium chloride on a silica surface were studied using an in situ quartz crystal microbalance with dissipation (QCM–D) coupled with contact angle measurements. Two electrolytes, NaCl and CaCl2, were used to investigate the effects of ionic strength (IS) and ion valence. The QCM–D data at different pHs, both with and without a background electrolyte, revealed complex changes in the collector conformations and structure of the adsorption layer. Two distinct adsorption characteristics were also observed depending on ion valence: the presence of NaCl led to a thin, rigid layer (low dissipation), while a thick, soft layer (high dissipation) formed in the presence of CaCl2 . Meanwhile, the increase in the IS of NaCl resulted in a more rigid adsorbed layer on the silica at both pHs. For CaCl2, the adsorbed layer became softer and highly dissipated at pH 5.7, whereas it became less soft at pH 10. This inconsistency in the rigidity with IS in the presence of CaCl2 was likely due to the strong sorption of Ca(OH) + at a high pH. Interestingly, the imparted hydrophobicity decreased as the IS increased, with a greater extent of reduction at a high pH regardless of ion type. Moreover, it had a strong relationship with the ratio of dissipation and frequency change, with a lower contact angle at a higher ratio due to greater imbibition of water molecules and/or hydrated cations. These findings have implications for silica flotation systems wherein Ca 2+ and Na + cations are present in appreciable amounts.